2014
DOI: 10.1158/0008-5472.can-13-3133
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin A Receptor/β-Arrestin Signaling to the Wnt Pathway Renders Ovarian Cancer Cells Resistant to Chemotherapy

Abstract: The high mortality of epithelial ovarian cancer (EOC) is mainly caused by resistance to the available therapies. In EOC, the endothelin-1 (ET-1, EDN1)-endothelin A receptor (ET A R, EDNRA) signaling axis regulates the epithelial-mesenchymal transition (EMT) and a chemoresistant phenotype. However, there is a paucity of knowledge about how ET-1 mediates drug resistance. Here, we define a novel bypass mechanism through which ET A R/b-arrestin-1 (b-arr1, ARRB1) links Wnt signaling to acquire chemoresistant and EM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 45 publications
10
107
0
Order By: Relevance
“…In orthotopic OC models, it has been demonstrated direct involvements of ET-1 axis in promoting metastatic phenotype (13,(23)(24)(25)(26)28). Moreover, deeper studies showed that the metastatic phenotype is linked to the ET A R-␤-arr1-mediated pathways.…”
Section: Role Of Et-1 In the Interactions Of Tumor Cells With The Micmentioning
confidence: 99%
See 4 more Smart Citations
“…In orthotopic OC models, it has been demonstrated direct involvements of ET-1 axis in promoting metastatic phenotype (13,(23)(24)(25)(26)28). Moreover, deeper studies showed that the metastatic phenotype is linked to the ET A R-␤-arr1-mediated pathways.…”
Section: Role Of Et-1 In the Interactions Of Tumor Cells With The Micmentioning
confidence: 99%
“…In particular, activation of the ET-1 pathway induces EMT through multiple distinct mechanisms, including the stabilization of the ␤-catenin protein, to engage transcription of genes related to EMT, through the ability of ␤-arr1 to serve as signal transducers in OC cells (23,25,26). Moreover, coexpression of ET A R and ␤-arr1 in human OC tissues is indicative of the malignant phenotype, and ET A R overexpression is associated with the switch of cadherin expression, indicating the relevant role of ET A R/␤-arr1 in the regulation of EMT and aggressive behavior (24,26).…”
Section: Role Of Et-1 In the Interactions Of Tumor Cells With The Micmentioning
confidence: 99%
See 3 more Smart Citations